What Is the Role of AI in Revenue Cycle Management? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2015)
Revenue Cycle Management (RCM) is a critical financial process for healthcare organizations, encompassing the management of all administrative and clinical f...
Keywords: Healthcare Administration and AI; Revenue; Cycle; Management; Artificial Intelligence; Machine Learning; Healthcare